Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Polynomials

Asked by hemant2020 25th March 2010, 4:10 PM
Answered by Expert
Answer:

x2  - p(x+1) - c

= x2  - px - (p +c)

Comparing with,

x2  - (α + β)x + αβ = 0

α + β = p

αβ = - (p +c)

Now, (α+1)(β+1) = αβ + α + β + 1 = p - p - c + 1 = 1 - c

(α+1)(β+1) = 1 - c

Regards,

Team,

TopperLearning.

 

Answered by Expert 28th March 2010, 7:00 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp